Maintenance of phonetic and phonological distance in the English and Korean back vowel contours of heritage bilinguals. (November 2021) - Cheng, Andrew
Abstract: Bilingualism research demonstrates that the potential merger of vowel categories across a speaker's two languages is affected by the age of acquisition of the second language. For heritage bilinguals, however, there is no clear L1 and L2, since they acquire their heritage language in early childhood, but become dominant in the mainstream language of society as adults. Heritage bilinguals may nevertheless will acquire distinct vowel systems in their two languages, rather than a merged system. In this study, the back vowels of California English and Seoul Korean, two varieties that are spoken by bilingual second-generation Korean Americans in California, were collected in natural speech. Formant measurements were analyzed using linear mixed effects regression modeling and generalized additive mixed modeling to see whether the vowels of each language were similar or different in their formant contours. As predicted, the bilinguals maintained distance between the vowels of both languages across their durations, and the phonological effects of coarticulation were found to be stronger in English than in Korean. The differences are attributed to "multicompetence" in heritage bilinguals' phonology (Cook, 2020), or the interrelationship of multiple systems that exist and interact in the bilingual mind without merging completely, in opposition to models that frame heritage bilingualism as inherently imbalanced in favor of the dominant language.